Thai generation y/millennial consumer health and wellness: An antioxidant beverage SEM analysis - Bundechanan, Niphon; Fongsuwan, Wanno (My University, 2017)
The health and wellness food and beverage market is projected to grow to $US1.1 trillion by 2019 with 1.8 billion technology enabled, health conscious Gen Y/Millennial consumers leading the way. This study investigates new ways of evaluating purchase intention using integrated marketing communications, brand equity, and brand attitude embracing new Internet-related mediums such as Facebook, Twitter, and Instagram and new devices such as smartphones and tablets. Modern brand equity campaigns must also be culturally aware as Generation Y Asian youth represent the consumer of tomorrow with many global brands embracing new technologies to grow their markets. From the results of the study conducted on a health-conscious segment of 280 Bangkok Generation Y/millennial consumers, it was determined that brand equity had the largest influence on purchase intention of antioxidants beverages. Value and quality also determine the success of sales with culture and technology playing a significant role in integrated marketing communications.
Keywords: Brand attitude; Brand equity; Health and wellness; Integrated marketing communications; Purchase intention